The Influence of Organizational Power on the Achievement of Entrepreneurship for Business Organizations An Analytical Study of the Views of a Sample of Managers in the Iraqi Ministry of Education - AL-Ghraibawy, Alaa Muhsin Khafeef (Journal of Economics and Administrative Sciences, 2022)
This research aims to study the influence of organizational power on the achievement of entrepreneurship for business organizations. It is an analytical study of the views of a sample of managers in the Iraqi Ministry of Education. The research highlights the contribution that can be made from the knowledge of the theory of business organizations in achieving organizational success. The organizational power of the organization contributes to achieving entrepreneurship in the business environment and achieving a competitive position in the work environment. The research dealt with two variables: the first is the independent variable, the organizational power in its dimensions (Expend Power, Structural Power, Prestige Power). And the second variable is the entrepreneurship of business organizations in their dimensions (initiative, investment opportunities, creativity). A sample of (32) directors of the Iraqi Ministry of Education was included, including the assistants of the general directors, departmental managers and the divisions at the ministry’s center. The questionnaire was adopted as a main tool for collecting data. The SPSS program was used to measure, analyze and test the hypotheses and interpret the results of the research and the existence of a correlation relationship and the relationship of significant effect of statistical significance between the organizational power entrepreneurship of the business organizations in the Iraqi Ministry of Education. A number of conclusions were reached, the most important of which is that the organizational power has the greatest impact on the achievement of entrepreneurship for the organization. It contributes to its stability, growth and reputation, and achieves success among leading sectors